Extraction of flux leakage and eddy current signals induced by submillimeter backside slits on carbon steel plate using a low-field amr differential magnetic probe - Zaini, M. A. H. P. a; Saari, M. M.; Nadzri, N. A.; Aziz, Z.; Ramlan, N. H.; Tsukada, K. (IEEE, 2021)
Magnetic Flux Leakage (MFL) and Eddy Current Testing (ECT) are commonly employed as the non-destructive evaluation (NDE) techniques used to detect defects within the steel. The MFL technique is advantageous in terms of deep defects detection, while the ECT technique excels in providing dense information regarding defects. In this work, artificial MFL and eddy current (EC) signals in ferromagnetic materials are studied, and an experimental magnetic probe that utilizes both techniques is developed for signal verification. The separation between MFL and EC signals is achieved by utilizing the phase-sensitive detection technique, implementing a dynamic referencing method as opposed to the conventional static phase referencing. A finite element method (FEM) based simulation is employed to study and verify the MFL and EC signals measured by the proposed magnetic probe. The proposed magnetic probe features highly sensitive anisotropic magneto-resistive sensors capable of measuring the MFL and EC signals induced by artificial slits of varying depths engraved onto a 2-mm carbon steel plate. Finite element simulations indicate different flux leakage patterns and eddy current signals detected in the vicinity of the back-side slits. A good agreement is observed between the simulated and the measured MFL and EC signals for the optimized frequency range of 110-210 Hz with the corresponding Lissajous curve for the detection of submillimeter back-side slits. The study has shown that the combination of MFL and EC signals can be successfully captured by an appropriate magnetic probe for an enhanced detection performance of back-side defects in ferromagnetic materials.